Summertime nitrate aerosol in the upper troposphere and lower stratosphere over the Tibetan Plateau and the South Asian summer monsoon region - Y. Gu; Y. Gu; H. Liao; J. Bian (Atmospheric Chemistry and Physics, 2016)
We use the global three-dimensional Goddard Earth Observing System chemical transport model (GEOS-Chem) to examine the contribution of nitrate aerosol to aerosol concentrations in the upper troposphere and lower stratosphere (UTLS) over the Tibetan Plateau and the South Asian summer monsoon (TP/SASM) region during summertime of year 2005. Simulated surface-layer aerosol concentrations are compared with ground-based observations, and simulated aerosols in the UTLS are evaluated by using the Stratospheric Aerosol and Gas Experiment II satellite data. Simulations show elevated aerosol concentrations of sulfate, nitrate, ammonium, black carbon, organic carbon, and PM2.5 (particles with diameter equal to or less than 2.5 µm, defined as the sum of sulfate, nitrate, ammonium, black carbon, and organic carbon aerosols in this study) in the UTLS over the TP/SASM region throughout the summer. Nitrate aerosol is simulated to be of secondary importance near the surface but the most dominant aerosol species in the UTLS over the studied region. Averaged over summertime and over the TP/SASM region, CNIT (the ratio of nitrate concentration to PM2.5 concentration) values are 5–35 % at the surface, 25–50 % at 200 hPa, and could exceed 60 % at 100 hPa. The mechanisms for the accumulation of nitrate in the UTLS over the TP/SASM region include vertical transport and the gas-to-aerosol conversion of HNO3 to form nitrate. The high relative humidity and low temperature associated with the deep convection over the TP/SASM region are favorable for the gas-to-aerosol conversion of HNO3.